先化简再求值[﹙6x+4分之1﹚﹙6x+4分之1﹚-﹙6x+4分之1﹚﹙6x-4分之1﹚+﹙2x+2分之1﹚﹙x-4分之
1个回答
原式=(36x²+3x+1/16-36x²+1/16+2x²-1/8)÷4x
=(2x²+3x)÷4x
=(2x+3)/4
=(2×(-1/2)+3)/4
=1/2
相关问题
(1)2x-1分之2=4x²-1分之4 (2)x²+x分之2x+1=6x+6分之5
先化简再求值:(x²-4x+4分之x-1 -x²-2x分之x+2)÷(x分之4 -1)其中x=-1
x+2分之1-x+4分之1等于x-6分之1-x-4分之1
2x4分之1+4x6分之1+6x8分之1.+2012x2014分之一
计算 x+2分之1+ x^2-4分之x+6 -x^-4x+4分之2x+1
解方程:X-4分之1X=16分之9 4分之1X+3分之1X=6分之5 6+4分之1X=18
1x2分之1+2x3分之1+3x4分之1+4x5分之1+5x6分之1+6x7分之1 等几?
2分之1x+6分之1x=4
2x4分之1+4x6分之1……2010x2012分之1=?为什么
6x-2乘4分之1=4分之5 2分之1+4分之1x=5分之3